L'AEROFOTOTECA NAZIONALE RACCONTA.... Pianura Pontina, 17 marzo 1944: la "slicing run” del tenente Dolk (GEOmedia, 2020)
On March 17, 1944 Lt. Carl E. Dolk of the USA Air Force took over the Pontineplain to the E of Anzio a number of aerial photos in what was called in militaryjargon a "dicer run". This was a highly hazardous low altitude flight that wouldenable the Allied command to decide how to overcome the German barrage.This set of photos is kept today by the Aerofototeca Nazionale in Rome.